Students’ Reasons for Preferences of Contexts in Learning Mathematics - Kazima, Mercy (Journal of Education and Training Studies, 2015)
This paper reports on findings from a study that investigated reasons Malawian students have for preferring particular contexts in mathematics. The study explored students’ preferences of contexts using a survey questionnaire that contained 27 contexts and asked students to indicate their level of interest for each context on a 4-point scale and to write down reasons for their most preferred contexts. There were 393 students of 14-20 years old. Findings include that most preferred contexts were of future career prospects, modern technology, health and community issues. Students’ reasons for these preferences were in four categories of career prospects, curiosity, community well-being and personal well-being. Furthermore, future career prospects was the most common reason for the preferred contexts.
KerkoCite.ItemAlsoKnownAs: 10.11114/jets.v3i3.687 4752638:B95GCEEL
Keywords: _C:Malawi MWI